FEMALE INFERTILITY: A CASE STUDY - Singh, Neetu; Dave, Hetal H; Chaudhary, Poonam (International Research Journal of Ayurveda & Yoga, 2024)
Infertility is an increasing problem among married couples. Due to this the couple who could not conceive become so much anxious , curious , stressed , that they are so much emotionally depressed due which the problem become more severe by affecting their psychosomatic health which further affects the HPO axis . Hence this becomes a major complex issue. As per ayurveda classics by taking hitkar aahara , vihara, which enhance dhatu, updhatu poshan which ultimately establishes dhatusamya avastha .Which result in enhaced quality of kshetra, ambu, beeja and after attaining these, in appropriate ritukal with proper following the regimen as per ayurveda the couple can not only conceive but also can achieve a healthy progeny.